Evaluating the accuracy of ICD-10 codes for syncytial respiratory virus diagnosis in hospitalized patients: A record-linkage study (2022–2023) - Ana Luiza Bierrenbach; Olivia Tavares Ranzani (PLoS ONE, 2025)
Background Respiratory Syncytial Virus (RSV) is a leading cause of severe respiratory infections in young children and older adults. Accurate RSV surveillance is essential to understanding its disease burden and evaluating vaccine impact. Methods We assessed the accuracy of ICD-10 coding for RSV hospitalizations in the Brazilian Hospital Information System (SIH) by linking it with the Severe Acute Respiratory Syndrome (SIVEP) notification system (2022–2023). Laboratory-confirmed RSV-positive and RSV-negative cases in SIVEP were used as the reference standard. Sensitivity and specificity were evaluated for ICD-10 definitions (RSV, RSV +  J21 [Acute Bronchiolitis], RSV +  Acute Respiratory Infection) overall and by age group (under 1 year, under 5 years, and over 60 years). The top 10 diagnoses of RSV-positive patients were also analyzed by age group. Results Among 15,169 RSV-positive patients linked to an SIH record, 73.0% were under 12 months old, 20.8% were 1-5 years old, 3.7% were 5-59 years old, and 2.5% were 60 + years. Acute bronchiolitis was the most common diagnosis overall (43.5%), particularly in infants (53.5%). In older adults, pneumonia due to unspecified microorganisms was most frequent (24.6%). Sensitivity improved with broader case definitions, such as, RSV +  Acute Respiratory Infection (66.7%, 95%CI: 65.8–67.6 in infants; 23%, 95%CI: 18.9–27.6 in older adults). Specificity was higher in older adults (83.8%, 95%CI: 83.5–84.1) than in infants (45.1%, 95%CI: 44.4–45.6). Additionally, 40,701 RSV-positive notified cases lacked RSV-coded diagnoses in SIH. Conclusion Our study highlights the discrepancy between RSV-positive cases identified in SIVEP and those coded in the SIH database, reflecting limitations in ICD-10 coding, particularly in the older population. Reliance on symptomatic coding rather than confirmed diagnoses contributes to this issue. Accurate RSV identification is crucial, especially with new vaccines available. Improved diagnostic coding is essential for effective RSV surveillance and evaluating vaccine impact.